Lower extremity reconstruction a practical guide - Hong, Joon Pio; Hallock, Geoffrey G. (Thieme, 2021)
"Adequate evaluation of lower limb wounds for salvage requires an itemized assessment of vascular, osseous, soft tissue, and functional deficits. Lower Extremity Reconstruction: A Practical Guide by renowned reconstructive surgeons and perforator flap masters J.P. Hong and Geoffrey G. Hallock presents an orthoplastic approach to this growing and challenging area of microsurgery. Throughout the well-illustrated text and videos, an impressive cadre of international surgeons share pearls and insights, including esoteric knowledge and step-by-step demonstration of techniques with pertinent case examples. This unique guide presents a practical, visual, and stepwise approach to learning and mastering a full array of flap and microsurgery approaches for traumatic, dysvascular, metabolic, and oncologic lower limb defects. Organized into 26 topic-specific chapters, the book covers a full spectrum of lower extremity topics-from wound prep, timing, closure alternatives, and therapy-to soft-tissue tumors and a new concept in drop foot treatment. Numerous videos demonstrate how surgeons can leverage workhorse options to prevent chronic non-healing wounds or amputations and achieve the goal of limb salvage"--